The Czech Concepts of East Central European Integration - Petráš, René (The Development of European and Regional Integration Theories in Central European Countries, 2022)
The beginning of this chapter analyzes the conditions of the creation of the Czech nation and its geographical position; the chapter then focuses on the Czech concepts of European integration, especially in the 19th and 20th centuries. In the past, the Czech or Czechoslovak state has been relatively significantly involved in efforts for international cooperation and integration processes. The difficult international situation of a state often surrounded by several hostile neighbors, as it was between the world wars, usually contributed to this. In the years 1526–1918, Czech lands were part of the Central European Habsburg monarchy. In the 19th century, the Czech national movement primarily considered two integration concepts. These were based on transforming the monarchy into the protector of small—especially Slavic—nations (Austroslavism) or, exceptionally, efforts to cooperate with powerful Russia (Pan-Slavism). Between 1918–1938, Czechoslovakia strived for international cooperation and European integration; from 1948–1989, it was part of the Soviet bloc. The fall of the communist regime in 1989 was a major advantage to the majority interest of the society to ‘return to Europe,’ symbolized by joining Western European organizations. KEYWORDS: Central European Habsburg monarchy; Austroslavism; Pan-Slavism; Czechoslovakia; Soviet bloc